Floodplain cocoa as an expression of amazonian socio-biodiversity: The experience of the Tocantins Integration Region, Pará - Cardoso Gaia, Shirlene (2025)
This article looks at cocoa as an expression of socio-diversity and cultural heritage in the Tocantins Integration Region, in the state of Pará, and aims to analyze how the production of floodplain cocoa articulates ancestral knowledge, territoriality and market insertion. The research adopts a qualitative and quantitative approach, based on bibliographical and documentary analysis and fieldwork carried out with leaders of cooperatives and community associations on the islands of Angapijó (Mocajuba), Tamanduá Costa (Cametá), and Arauaia (Barcarena), located in the area's floodplain. The results indicate that floodplain cacao plays a significant role in generating income, environmental conservation, and preserving cultural identity. The conclusion is that the ancestral cocoa of the Tocantins region is an important asset, a vector for socio-territorial development, and a symbol of the resistance of the peoples of the forest, requiring public policies aimed at protecting and adding value to the product.